Peran Ibu Rumah Tangga dalam Membangun Kesejahteraan Keluarga - Septi Latifa Hanum (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This paper would like to analyze the housewives' efforts in the rural area and its contribution in building family welfare. This research uses descriptive qualitative approach, data obtained by interviewing 6 informants in Pucangan, Kartasura, Sukoharjo. The results show that housewives have special tips in managing the income from the husband for the household welfare. In addition, housewives also look for additional jobs to increase family income in order to improve household welfare. Thus, the effort to make the family prosperous depends not solely on the husband's ability, but the wives also have a role that together builds the family welfare.Keywords: housewife, village, welfare, family